Effects of diabetes on cytokines and oxidative organ injury in a rat model of sepsis - Uyanik, M. H.; Albayrak, A.; Odabasoglu, F.; Karakus, E.; Ozden, K.; Polat, B.; Yayla, M.; Karamese, M.; Albayrak, A.; Yazgi, H. (Cellular and Molecular Biology, 2012)
We aimed to investigate how Diabetes Mellitus (DM) affects myeloperoxidase activity, antioxidant status, and lipid peroxidation using biochemical approaches in heart, liver, and lung and serum cytokine analyses, such as interleukin-6 (IL-6) and tumor necrosis factor-Î± (TNF-Î±) in rat with sepsis induced by a cecal ligation and puncture-induced (CLP) sepsis. The rats were divided into four groups: control group, diabetic group, sepsis group, and diabetic+sepsis group. DM was induced in the male Wistar albino rats by administration of alloxan. Polymicrobial sepsis was induced by cecal ligation and two-hole puncture. After alloxan administration, all groups of rats were allowed to recover for 1 month. CLP model was applied after 1 month recovery to group 3 and 4. IL-6 and TNF-Î±, were measured. Effects of antioxidant defenses on the DM and/or sepsis process, the antioxidant levels superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) were evaluated in heart, lung and liver tissues. The oxidant levels, such as lipid peroxidation (LPO) and myeloperoxidase (MPO) levels were also evaluated in tissues. We demonstrated DM to augment the level of oxidant and proinflammatory cytokines in lung, liver, and heart and also to exacerbate oxidative injury as assessed by increased LPO and MPO, and decreased GSH and SOD levels in a sepsis model. DM increased levels of proinflammatory cytokines while DM also resulted in significantly increased levels of proinflammatory cytokines following CLP. DM-increased plasma proinflammatory cytokines levels correlated positively with tissue oxidant levels, such as MPO and LPO levels in a rat abdominal sepsis model, based on CLP, which resulted in the exacerbation of oxidative organs injury.